Effects of Lupeol on Estrogen and Androgen Receptor-Positive Breast and Prostate Cancer Cells : Lupeol in ER+ and AR+ BC and PC cells - Nezami Majd, Mahdieh; Alizadeh, Arash; Zadeh Hashem, Elham (Archives of Breast Cancer, 2024)
Background: Different reports have shown that prostate and breast cancers are the most common cancers worldwide. Lupeol, a dietary triterpene, provides various beneficial effects including anti-cancer properties. The current study aims to investigate the anti-proliferative and antioxidant effects of lupeol, in line with the effects of lupeol on the expression of estrogen and androgen receptors in breast (MCF-7) and prostate (LNCaP) cancer cell lines. Methods: MCF-7 and LNCaP cells were incubated with increasing concentrations of the lupeol (1, 10, and 100 µM) for 24h. The cytotoxicity of the lupeol was assessed by MTT and Neutral Red assays. Moreover, TAC (total antioxidant capacity), and gene expression of androgen and estrogen receptors were measured by spectrophotometric and qPCR methods, respectively. Overall, 17 beta-estradiol (E2) (9 nM) and dehydroepiandrosterone (DHEA) (5 µM) were selected as positive controls. Results: The highest concentration of the lupeol induced cytotoxic effects on MCF-7 and LNCaP cells. Various levels of lupeol at specified time intervals increased TAC levels in comparison with the control group. Moreover, the expression levels of estrogen receptors (α and β) and androgen receptors were negatively affected by lupeol. Conclusion: The findings of our study indicate that lupeol could serve as a promising, and accessible multi-functional anti-tumor agent against hormone-positive breast and prostate cancers.